Challenge Testing to Determine Growth of Listeria monocytogenes on Fresh Enoki Mushrooms at 4 °C and 10 °C Storage Temperatures - Jacqueline P. Upham; J. Austin Markell (Journal of Food Protection)
Recent listeriosis outbreaks and recalls related to high prevalence and counts of Listeria monocytogenes in enoki mushrooms imported from South Korea and China represent a current food safety concern. Unlike domestically produced mushrooms, imported products are often packaged without free air exchange and are associated with a longer shelf life. The present study used challenge tests to investigate the potential for harvested enoki mushrooms stored under refrigeration to support the growth of L. monocytogenes, to better inform food safety regulators of the risk associated with low levels of L. monocytogenes on enoki mushrooms ready for retail. Counts of L. monocytogenes rose significantly on enoki mushroom portions from 30 to 1,000 CFU/g within 4 days at 10 °C (n = 202) and 9 days at 4 °C (n = 138). Curve fitting into the Baranyi growth model indicated a 100-fold increase in 3.7 days (10 °C) and 8.8 days (4 °C). Additional factors examined in the study included the effect of the presence of residual mushroom growth substrate and Listeria innocua as enoki background microbiota. L. innocua was associated with significantly (p < 0.001) lower maximum levels of L. monocytogenes during challenge tests at 10 °C. High prevalence of L. innocua was observed on imported enoki (15 of 18 lots) and is of concern as this species shares environmental niches with L. monocytogenes and thus a risk factor; monitoring for it should be promoted. L. monocytogenes growth on enokis was accelerated when residual enoki growth substrate was present, with a significant (p < 0.05) impact on L. monocytogenes levels by Day 2 at 10 °C and Day 3 at 4 °C, which prompts consideration for removing substrate before packaging. Finally, small-scale sampling suggests a lack of consistency in baseline contamination of L. monocytogenes among individual packages of the same lot, of interest with regards to sampling approaches for imported enoki mushrooms prior to retail.